2015
DOI: 10.1136/bjophthalmol-2015-307043
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and visual function outcomes in paediatric idiopathic intracranial hypertension

Abstract: Clinical observation of high papilledema grade on presentation is predictive of poor visual outcomes. Vision loss is associated not only with optic atrophy but also with photoreceptor damage. Interestingly, a high proportion of study eyes had optic disc drusen, which was not associated with vision loss, but can be a diagnostic challenge in distinguishing true papilledema from pseudopapilledema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 26 publications
2
34
0
1
Order By: Relevance
“…The high rate of ODD in IIH with resolved papilloedema at almost 10 times higher than expected in the general population suggests that the coexistence of ODD and IIH is not random. Interestingly, a 2016 report from Gospe et al 30 identified 48% (13 of 27) of their pediatric IIH cases having evidence of buried ODD on OCT after papilloedema had resolved. It is uncertain if the development of ODD is more likely to occur when papilloedema from IIH develops in the prepubescent period as compared with an older age of IIH onset.…”
Section: Discussionmentioning
confidence: 99%
“…The high rate of ODD in IIH with resolved papilloedema at almost 10 times higher than expected in the general population suggests that the coexistence of ODD and IIH is not random. Interestingly, a 2016 report from Gospe et al 30 identified 48% (13 of 27) of their pediatric IIH cases having evidence of buried ODD on OCT after papilloedema had resolved. It is uncertain if the development of ODD is more likely to occur when papilloedema from IIH develops in the prepubescent period as compared with an older age of IIH onset.…”
Section: Discussionmentioning
confidence: 99%
“…They found permanent visual acuity or visual field loss in 19% of the children, and highly correlative with vision loss was OCT findings of optic atrophy in 13% and photoreceptor loss in 19% of the children. 59 In an evaluation of 56 children with IIH, Agarwal et al found 17% had poor visual acuity outcome (worse than 20/200 vision) and 41% had poor visual field testing at 6 months. 69 Predictors of permanent vision loss are severe swelling, severe visual field/acuity loss, and high opening pressure at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…69 Predictors of permanent vision loss are severe swelling, severe visual field/acuity loss, and high opening pressure at presentation. 58,59,69…”
Section: Discussionmentioning
confidence: 99%
“…96,98 Similarly, OCT can be used to diagnose and monitor pediatric pseudotumor cerebri and is potentially useful as a visual prognostic tool in this condition. 99,100 An increased central macular, temporal, and superior RNFL thickness has been described in children affected by pseudotumor cerebri. 101 The presence of optic atrophy and photoreceptor loss on OCT in pseudotumor cerebri are findings that are highly associated with irreversible visual loss.…”
Section: Optic Nerve Pathologymentioning
confidence: 99%
“…101 The presence of optic atrophy and photoreceptor loss on OCT in pseudotumor cerebri are findings that are highly associated with irreversible visual loss. 100 Interestingly, optic nerve parameters may also be predictive of central nervous system development and pathology, with larger vCDR being associated with lower Bayley Scales of Infant Development scores. 28,33 A weak association has been described between a larger vertical cup diameter (vCD) and vCDR with periventricular leukomalacia, and a shallower cup with posthemorrhagic hydrocephalus.…”
Section: Optic Nerve Pathologymentioning
confidence: 99%